2004
DOI: 10.1191/0961203304lu480oa
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and factors associated with fibromyalgia in Mexican patients with systemic lupus erythematosus

Abstract: In total, 189 consecutive women diagnosed with SLE were evaluated using the ACR 1990 criteria for fibromyalgia. Patients were classified into three subgroups. The fibromyalgia group (FM) included patients experiencing pain on palpation in at least 11 of the 18 tender points examined, as well as having a history of widespread pain for at least three months. Patients who were noted to have pain in fewer than four quadrants with less than 11 of 18 tender points were considered to have regional pain (RP). All pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
3
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 23 publications
2
22
3
3
Order By: Relevance
“…In an Indian tertiary referral center cohort, Handa et al found fibromyalgia in 8.2% of 158 patients (6). In a Mexican clinic, Valencia-Flores et al reported 9.5% of 106 SLE patients satisfied ACR criteria (7). In the LUMINA (lupus in Minorities) study, Friedman et al reported a prevalence of fibromyalgia of 5% in 266 SLE patients (8).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In an Indian tertiary referral center cohort, Handa et al found fibromyalgia in 8.2% of 158 patients (6). In a Mexican clinic, Valencia-Flores et al reported 9.5% of 106 SLE patients satisfied ACR criteria (7). In the LUMINA (lupus in Minorities) study, Friedman et al reported a prevalence of fibromyalgia of 5% in 266 SLE patients (8).…”
Section: Discussionmentioning
confidence: 99%
“…The issue of SLE and fibromyalgia has been approached by a number of investigators (3)(4)(5)(6)(7)(8)(9). Two approaches to the problem have included trying to distinguish persons with fibromyalgia from those with SLE and identifying persons with SLE who also have fibromyalgia.…”
mentioning
confidence: 99%
“…10 A literatura já apontou uma maior prevalência de FM mais em pacientes com LES do que na população geral. A prevalência identificada de FM nos pacientes com LES no presente estudo foi de 12%, discretamente menor do que a encontrado na literatura, [16][17][18][19][20][21][22] que varia entre 17% e 22%. À avaliação das características da dor e a intensidade dos sintomas por meio dos questionários EVA, IDG e ISS, observaram-se os piores desempenhos nos grupos que apresentam FM isolada ou associada.…”
Section: Discussionunclassified
“…15 A associação da FM e do LES tem sido investigada por vários autores, com resultados conflitantes em relação ao impacto de uma condição na outra. [16][17][18][19][20][21][22] A prevalência da associação da concomitância entre as duas doenças encontra-se em torno de 20%. 16 Assim, a presença de FM em pacientes com LES é muito maior do que na população geral.…”
Section: Introductionunclassified
“…Moreover, in this series no significant correlation was observed in SLEDAI (r= +0.085, p = 0.495) with disease duration as shown in Table-VII. 15 . They observed nearly similar mean ages among the 3 subgroups (37.8±11.3, 39±13.4 and 39.8years respectively).…”
Section: Correlates Of Fibromyalgia Tender Points and Disease Activitymentioning
confidence: 99%